2016
DOI: 10.1016/j.cub.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscience: A Distributed Neural Network Controls REM Sleep

Abstract: Considerable advances in our understanding of the mechanisms and functions of rapid-eye-movement (REM) sleep have occurred over the past decade. Much of this progress can be attributed to the development of new neuroscience tools that have enabled high-precision interrogation of brain circuitry linked with REM sleep control, in turn revealing how REM sleep mechanisms themselves impact processes such as sensorimotor function. This review is intended to update the general scientific community about the recent me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 158 publications
1
29
0
Order By: Relevance
“…It is our working hypothesis that RBD is caused by synucleinopathic degeneration of this 2‐part brain stem circuit (Fig. ), and this assertion is supported by the fact that lesions of the so‐called “REM sleep circuit” can cause RBD‐like motor behaviors in both animals (cats, rats, mice) and humans …”
Section: Mechanisms Controlling Rem Sleep Paralysismentioning
confidence: 93%
See 1 more Smart Citation
“…It is our working hypothesis that RBD is caused by synucleinopathic degeneration of this 2‐part brain stem circuit (Fig. ), and this assertion is supported by the fact that lesions of the so‐called “REM sleep circuit” can cause RBD‐like motor behaviors in both animals (cats, rats, mice) and humans …”
Section: Mechanisms Controlling Rem Sleep Paralysismentioning
confidence: 93%
“…Therefore, the subcoeruleus nucleus and ventromedial medulla constitute “the core” REM sleep circuit, with glutamate cells in the subcoeruleus nucleus functioning as the “master REM sleep switch” (Fig. ).…”
Section: Mechanisms Controlling Rem Sleep Paralysismentioning
confidence: 99%
“…In mammals, slow waves are generated by thalamocortical interactions [Steriade et al, 1993;Lemieux et al, 2014]. REM sleep-related cortical activation, reduction in muscle tone, and eye movements are all controlled by the brainstem [Siegel, 2011;Luppi et al, 2013;Weber et al, 2015] and its interactions with a network of other brain structures throughout the neuroaxis [Jego et al, 2013;Luppi et al, 2015;Peever and Fuller, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the similarities of the EEG spectrum and muscle atonia features, cataplexy has long been considered as a REM sleep intrusion into waking or abnormal REM sleep during waking (Luppi et al, 2011;Roth et al, 1969). Indeed, studies have found that cataplexy and REM sleep share some common neural substrates (Dauvilliers et al, 2014;Peever et al, 2016;Thakkar et al, 1999). Thus, MCH neurons, an important REM sleepregulating hub, are thought to trigger intrusions of REM sleep bouts into waking in the absence of orexin, consequently resulting in cataplexy.…”
Section: Discussionmentioning
confidence: 99%